The Influence of Compensation and Work Motivation on Teacher Performance with Work Quality as an Intervening Variable in Vocational High Schools across Grogol Petamburan District, West Jakarta - khairani khairani; Corry Yohana; Christian Wiradendi Wolor (Journal of Management Economics and Financial Accounting, 2026)
This study aims to analyze the effect of compensation and work motivation on teacher performance with work quality as an intervening variable among vocational high schools (SMKs) in Grogol Petamburan District, West Jakarta. This study employed a quantitative approach with a causal associative research design. The population consisted of 304 teachers from 15 vocational high schools, with a sample of 173 respondents determined using the Yamane formula with a 5% margin of error and proportionate random sampling. Data were collected through questionnaires using a Likert scale and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS 3. The results showed that compensation had a positive and significant effect on teacher performance, work quality, and teacher performance through work quality as an intervening variable. Work motivation also had a positive and significant effect on teacher performance and work quality, as well as a positive and significant indirect effect on teacher performance through work quality as an intervening variable. The strongest direct effect was found in the relationship between work quality and teacher performance, with a path coefficient of 0.803. These findings indicate that improving teacher performance is influenced not only by compensation and work motivation directly but also through the improvement of work quality as an important mechanism in enhancing teacher performance.